A revision of Cousinia sections Alpinae (syn. Carduncellus), Subappendiculatae and Tianschanicae (Asteraceae) in the Kirghizian Tian-Shan and the neighbouring territories - Sennikov, Alexander N. (Phytotaxa, 2013)
The species of Cousinia currently assigned to C. sections Carduncellus and Subappendiculatae in the Kirghizian part of the Western Tian-Shan are revised and reclassified using the characters of phyllaries and anther appendages. The shape of the apical anther appendages is found species-specific and taxonomically useful, as exemplified by the description of two new species from Kirghizia, Kazakhstan and Uzbekistan, formerly included in C. tianschanica. Following the differences in the apical and the basal anther appendages, C. section Carduncellus is split with the description of a new section C. section Tianschanicae and renamed in order to restore the older name, C. section Alpinae. Cousinia knorringiae is moved from C. section Carduncellus to C. section Subappendiculatae, and C. omissa from C. section Subappendiculatae to C. section Tianschanicae. The species limits and distribution areas are corrected, C. fetissowii is reported as new to Uzbekistan and several species as new to particular mountain ranges. A complete taxonomic treatment of 9 species with an identification key, descriptions, maps and typifications is provided, and the distribution areas are discussed.